Evaluation of the organization of the Syrian athletics championships for 2019 - صقر, رشا; الخليل, امجد (Latakia University Journal -Medical Sciences Series, 2021)
The Objective evaluation based on a scientific reveals the extent of achieving organizational goals and success,and thus helps to make decisions that will raise the level of organizing tournaments, And show cases of strength in the organization and strengthen them and indicate weaknesses to address them, which contributes effectively to the development of the organizational management of tournaments, The researchers used the descriptive approach using the survey method, to research sample consists of the data for the Syrian Athletics Championships for the 2019, which are three tournaments (the Baraem Championship in Sweida, Republic Championship in Damascus, Syrian Olympics Championship in Lattakia), Then an evaluation scale was applied to organize athletics tournaments for researchers Jawad and Al-Janabi (2012), the scale includes four axes, (Arbitration - technical - coordination or administrative - financial and media) and consists of (54) statements, and The study found that all resident tournaments suffer from weakness in organization, and The administrative field is the highest organized relative to other axes, and The media and financial sphere it is the least organization relative to the other axes, as It was noticed that the randomness of the organization between one tournament and the other of the same regulator, And the lack of media coverage of the required level on all aspects.